Compatibility of the Curricula of Public Medicine Internship and Apprenticeship Programs with General Practitioners' Roles and Responsibilities - Mehrangiz Ghasemie; Mahasti Alizadeh; Zhila Khamenian; Javaher Yari (Kerman University of Medical Sciences, 2017)
Background and Objectives The aim of the present study is to investigate the compatibility of public medicine internship and apprenticeship curricula with roles and responsibilities of general practitioners (GPs) from their personal perspectives at health centers, affiliated to Tabriz University of Medical Sciences, Tabriz, Iran. Methods This cross sectional analytical survey was performed on 80 GPs in East Azerbaijan province, Iran in 2014 via simple random sampling. The data collection tool included a researcher-made questionnaire, based on the curricula of community medicine internship and apprenticeship programs and a focus group discussion about GPs' responsibilities. The content validity and reliability of the questionnaire were confirmed by professionals and experts of public health education. For data analysis, descriptive statistics (mean, standard deviation, frequency, and percentage) and one-sample t test were performed, using SPSS. Results On average, more than 83% of GPs in this study believed that subjects presented in public medicine internship and apprenticeship programs should remain in the curricula. More than 60% of GPs demanded the integration of subjects, including professional ethics and approaches towards preventive medicine and disease risk factors, in the internship program. In addition, more than 50% of GPs asked for the integration of accurate drug prescription and test administration in the internship program. Generally, the respondents reported a moderate to high level of compatibility between the educational content of internship (mean, 3.3 ± 0.74; minimum, 1.1; maximum, 5) and apprenticeship (mean, 3.13 ± 0.77; minimum, 1; maximum, 4.92) programs. Conclusions According to the results, GPs reported a medium to high level of compatibility between the curricula of internship and apprenticeship programs, as stated by GPs. They also asked for the integration of certain subjects in their curricula. Therefore, it is essential to coordinate the educational syllabus with the actual medical education needs of students in order to improve GPs' efficiency and promote a community-based approach in medical education.